OP0230 Systemic Vasculitis and Pregnancy: A Multicenter Study on Maternal and Neonatal Outcome of 66 Prospectively Followed Pregnancies. (10th June 2014) - Lazzaroni, M.G.; Fredi, M.; Andreoli, L.; Brucato, A.; Caporali, R.; Caramaschi, P.; Doria, A.; Gerosa, M.; Guillevin, L.; Inverardi, F.; Lojacono, A.; Meroni, P.L.; et al.
Abstract : Background: Systemic Vasculitis (SV) are rare diseases and unlike other rheumatic diseases they do not preferentially affect women during reproductive age. A few data are available in literature, mostly from case reports with retrospective design [1, 2]. Objectives: Aim of our study is to prospectively evaluate maternal/neonatal outcome and disease course before, during and after pregnancy in patients with SV. Methods: 66 pregnancies in 44 women with diagnosis of SV (according to CHCC and or ACR criteria) were prospectively followed by a multispecialistic team composed by Rheumatologists, Gynecologists and Neonatologists in one of the 8 Institutions involved in a period comprised between years 1995 and 2013. Data were retrospectively collected from clinical charts using a common database. Data about a control population of 3939 healthy women in one center during one year (General Obstetric Population, GOP) were considered to compare the rate of pregnancy-related complications. Results: Outcome of pregnancy was 55 live births (85, 9%), 8 miscarriages before 10° week (12, 5%) and 1 fetal death after 10° week (1, 5%); 2 pregnancies are still ongoing. Data about pregnancy-related complications were compared to GOP: in SV patients preterm deliveries (20, 0% vs 11, 9%), severe (<34°weeks) preterm deliveries (10, 1% vs 5, 0%) and cesarean section (47, 3% vs 31, 0%) were significantly more frequent than in GOP. Disease-related complications occurred in 24 pregnancies during the three trimesters (36, 4%), with 8 severe events (12, 1%) including 3 cases of transient ischemic attack. Data about the postpartum period were available for 51 pregnancies: 11 flares (21, 6%) occurred, with 1 severe event (1, 9%). Conclusions: SV patients can have successful pregnancies, but with increased risk of preterm delivery. Pregnancy-related modifications (immunological, cardiovascular and thrombophilic) can negatively affect the course of disease, with severe complications. A tight control by a multispecialistic team should be a standard in pregnancies of women with SV. References: Gatto M et al. Pregnancy and vasculitis: a systematic review of the literature. Autoimmunity reviews 2012;11(6):A447-A459 Pagnoux C, Mahendira D, and Laskin CA. Fertility and pregnancy in vasculitis. Best Practice & Research Clinical Rheumatology 2013;27(1):79-94 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2312